An observational study on the effects of early and late risk factors on the development of childhood obesity in the South of Italy (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Child obesity is today one of the greatest health emergencies, on such a large scale as to be considered a global epidemic by the WHO and, unfortunately, Italy holds the worst European record.Methods: We conducted an observational study to investigate the effects of early and late risk factors on the development of primary childhood obesity. We collected anthropometric parameters, information about early risk markers and late risk factors on a sample of 280 children from March 2016 to December 2017.Results: Statistically significant associations emerged between: child's BMI and education level of the mother (p